Predict-Observe-Explain Learning Model Assisted by “Educandy” Games to Improve Students’ Conceptual Understanding - Zulhelmi, Zulhelmi; Syaflita, Dina; Amelia, Nurul Chandra; Sohibun, Sohibun (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2023)
A good understanding of concepts is needed to prevent students from misunderstanding. One effort that can be done is to apply the POE (Predict-Observe-Explain) learning model with the help of the Educandy educational game. This study aims to measure the effect of applying the POE learning model with the help of Educandy educational game application to increase students’ conceptual understanding of temperature and heat subjects. This study was quasi-experimental design research, using the nonequivalent control group design. The population of this study was 128 junior high schools students of SMPN 25 Pekanbaru (Class VII.I-Class VII.4). The first class, VII.1, was used as the experimental class, the third class, VII.3, was used as the control class, while the other class was the generalization classes. Research instrument of pretest and post-test containing 28 questions was used. The result was processed by descriptive and interferential techniques using T-test. The data processing technique used was descriptive and inferential, using the t-test for N-gain as an evaluation method. The results of this study indicated that conceptual understanding in both classes had increased, but the average value of students’ conceptual understanding in the experimental class was higher than that in the control class. It was described on the data N-gain as 0.7 in the experiment and 0.3 in the control class. The results of the t-test show that the POE learning model assisted by educational games based on the Educandy application can significantly improve students’ understanding of concepts.